The Effect of Risk Communication Process to Limit the Spread of the Covid-19 Pandemic Infection: Saudi Arabia as a Model - Alrashidi , Yousif; Missoui , Yosra (The Arab Journal of Administration, 2023)
This research studied the Risk Communication Process and its role and effect in reducing and limiting the spread of the pandemic of the COVID-19, while clarifying its principles, theories and the role it plays during health risks, specifically during the pandemic. The research aims to shed light on the importance of Risk Communication during pandemics and risk communication process in the Kingdom of Saudi Arabia and to assess its effectiveness and role in limiting the spread of the new Coronavirus pandemic infection, where the role of all stakeholders (government, experts and the public) will be highlighted. In order to achieve the objectives of the research, the two researchers relied on qualitative analysis through case studies and investigating efforts related to risk communication by the Ministry of Health. Also, content analysis and personal interviews with specialists in the field of communication and marketing in the Ministry of Health and the private sector were adopted as means of data collection. The results of this study indicate that the Saudi government, and specifically the Ministry of Health, was keen to apply the most prominent principles of effective risk communication, as the process during the Coronavirus pandemic is characterized by the speed of response, density of content and publication, continuity, diversity and transparency, which made it play an effective role in limiting the spread of the infection and dealing with the pandemic in a distinctive way. The results of the study also proved that communication between the government, the public and experts was based on a high degree of transparency, credibility and participation, due to the government’s keenness to empower experts and activate their role in the risk communication process to exchange accurate and scientific information to combat misinformation and rumors. The results of the study also showed the government’s keenness to involve the public and leaders and raise the level of interaction through diversity in content, targeting various groups, and continuous interaction with them through many platforms and through diversity in informative and awareness-raising content to communicate risks during the pandemic. The study was concluded by giving the most important recommendations to communication professionals, media professionals and marketers to ensure effective risk communication that contributes to resisting the spread of this epidemic and reducing its damage in light of the emerging corona pandemic.